From fracture to religare: Silvestre's technique and eco-poetics of the body in the face of the ecological-colonial crisis (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article analyzed the Silvestre Technique as a dialogical ecopoetics between body, art, and cosmos, highlighting how corporeality acts as memory, territory, and possibility. It investigated the relationship between body, culture, and nature in the face of the Anthropocene and Capitalocene, showing that African, Afro-diasporic, and indigenous knowledge stand out as ancestral responses to contemporary questions. The research highlighted that the arts not only express culture, but also actively participate in the formation of cosmoperceptions and civilizational values. Thus, the living arts are pointed out as laboratories of resistance and devices for building sustainable, ethical, and interdependent worlds.
Keywords: silvestre technique; ecopoetics; critical ecology; traditional knowledge; cultural studies